Pengembangan keterampilan Biopreneur siswa SMAIT Al-Fitriyan melalui pelatihan pembuatan keju menggunakan Asam Kandis: Developing Biopreneur Skills of SMAIT Al-Fitriyan Students through Cheese Making Training Using Asam Kandis - Mahwar Qurbaniah; Hanum Mukti Rahayu; Ahmad Faisal Amri; Dilla Khastuti (Universitas Hamzanwadi, 2024)
Learning in the industrial era 4.0 requires students to be able to have critical thinking skills, creative, communicative, collaborative, meaningful, interesting, applicable, adaptive, and contextual, and have selling points to foster student entrepreneurship. Biology is one of the subjects that can be applied to foster students' entrepreneurial spirit through Biopreneur activities. The entrepreneurial attitude of students cannot just grow but must be instilled early. Based on the results of observations and interviews with biology teachers at SMAIT AL-FITYAN Kubu Raya, information was obtained that students had never been given learning about biopreneurs. Therefore, it is necessary to carry out Biopreneur service activities for making cheese using kandis acid as a coagulant to replace rennet to foster students' entrepreneurial attitudes at SMAIT AL-FITIYAN. The methods that will be used in the service activities are; giving pre-test, socialization activities about cheese and the use of kandis acid; cheese making training; and evaluation of service activities by giving post-tests and response questionnaires. Based on the results of the questionnaire analysis, information was obtained that 100% of the participants had never participated in similar activities and thought that the material provided was new and the material that had been given was easy to practice again. As for the clarity of the material, the participants gave a very good response with a score of 81.25%. Participants also gave a very good response with a score of 100% regarding the location of activities that were easy to reach. For the services provided by the committee, participants gave a very good response of 100%. Based on the results of the activity, it can be concluded that the training provided was able to increase the participants' knowledge by 12.8% and the average participant response to the activity was 90.62% with a very good category. Thus, the training conducted can run effectively